Empirical models challenging biblical criticism - Person, Raymond F. 1961-; Rezetko, Robert 1967- (Atlanta SBL Press, 2016)
Cover; Contents; Abbreviations; Introduction; Outsourcing Gilgamesh; Scribal Revision and Textual Variation in Akkadian Suila-Prayers ; Dissimilatory Reading and the Making of Biblical Texts; Text-Critically Studying the Biblical Manuscript Evidence; Division Markers as Empirical Evidence for the Editorial Growth of Biblical Books ; The Problem of "Literary Unity" From the Perspectives of the Study of Oral Traditions ; The (Dis)Connection between Textual and Linguistic Developments in the Book of Jeremiah ; The Original Problem; Community Rule or Community Rules
Limited Efficacy in Reconstructing the Gospel Sources for Matthew and Luke Bibliography; Contributors; Ancient Sources Index; Modern Authors Index
"Empirical models based on ancient Near Eastern literature and variations between different textual traditions have been used to lend credibility to the identification of the sources behind biblical literature and the different editorial layers. In this volume, empirical models are used to critique the exaggerated results of identifying sources and editorial layers by demonstrating that, even though much of ancient literature had such complex literary histories, our methods are often inadequate for the task of precisely identifying sources and editorial layers"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Redaction -- History; Bible; Classical literature -- History and criticism; RELIGION ; Biblical Studies ; Exegesis & Hermeneutics; Classical literature; Criticism, interpretation, etc; History; Electronic books; Aufsatzsammlung